Nephrotoxicity of Kalach 360 SL: biochemical and histopathological findings. (21st November 2016) - Hamdaoui, Latifa; Naifar, Manel; Mzid, Massara; Ben Salem, Mariem; Chtourou, Amel; Makni-Ayadi, Fatma; Sahnoun, Zouheir; Rebai, Tarek
Abstract: Kalach 360 SL (KL) is a commercial herbicide which contains 360 g/l of glyphosate used in both agricultural and urban areas throughout the world including Tunisia. We aimed to evaluate the effects of KL on rats' renal system. Female Wistar rats were divided into three groups: group 1 ( n  = 6) received a standard diet and served as control, groups 2 and 3 ( n  = 12 each) received 0.07 ml (D1: 126 mg/kg), and 0.175 ml (D2: 315 mg/kg) of KL, respectively, for 60 d. The chronic exposure to KL induced a significant increase in plasma creatinine, urea, and uric acid levels. Creatinine clearance decreased in KL-treated groups, compared with controls. Several urine parameters, such as urine-specific gravity and urine osmolality, significantly decreased, while dieresis and urinary Na/K + ratio increased in KL-treated groups. These findings suggested a distal tubular damage caused by tubular necrosis. Moreover, the chronic exposure to KL induced an increase in lipid peroxidation (LPO) and a decrease in antioxidant status, enzymatic activities (superoxide dismutase and catalase) and non-enzymatic levels (vitamin C), which led to an oxidative stress. Histopathological studies showed a peritubular inflammatory reaction, nephrose, fragmented glomeruli, necrotic epithelial cells, and tubular dilatation. These results could have significant health implications for animal and human populations. Further data are necessary to investigate the potential consequences of chronic dose exposure during life.